Analisa Penggunaan Mesin X-Ray Sebagai Security System Di Bandara Internasional Husein Sastranegara - Galih Abu Ayub (Jurnal JE-UNISLA : Electronic Control, Telecomunication, Computer Information and Power System, 2021)
Security system is a protection has a structured cycle, meaning that it has been systemized according to its application in the environment according to its field. Security system is formed is because of threats, crimes and others. A security system is needed at certain events and in special places such as malls and airports to maintain the continuity of the event and security can be well maintained. Everyone who comes to the location must have their luggage checked to minimize the presence of sharp objects that endanger or threaten security at the location. Inspection of passenger objects at the airport is one way to protect the safety and security of airplane passengers. The procedure for checking objects carried by passengers is still carried out manually by airport security officers. The goal is to check whether you find sharp objects or illegal drugs in the passenger's bag. The results of this study are the authors know the working principle and operation of x-ray machines, as well as the number and types of x-ray machines used by Husein Sastranegara International Airport. Security system is a protection has a structured cycle, meaning that it has been systemized according to its application in the environment according to its field.Security system is formed is because of threats, crimes and others. A security system is needed at certain events and in special places such as malls and airports to maintain the continuity of the event and security can be well maintained. Everyone who comes to the location must have their luggage checked to minimize the presence of sharp objects that endanger or threaten security at the location. Inspection of passenger objects at the airport is one way to protect the safety and security of airplane passengers. The procedure for checking objects carried by passengers is still carried out manually by airport security officers. The goal is to check whether you find sharp objects or illegal drugs in the passenger's bag. The results of this study are the authors know the working principle and operation of x-ray machines, as well as the number and types of x-ray machines used by Husein Sastranegara International Airport.